2019
DOI: 10.21149/10373
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening in low- and middle- income countries: the Mexican case

Abstract: Prostate-specific antigen (PSA)-based early detection for prostate cancer is the subject of intense debate. Implementation of organized prostate cancer screening has been challenging, in part because the PSA test is so amenable to opportunistic screening. To the extent that access to cancer screening tests increases in low-and middle-income countries (LMICs), there is an urgent need to thoughtfully evaluate existing and future cancer screening strategies to ensure benefit and control costs. We used Mexico's pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…During this same year, there were an estimated 1.41 million cases and 486,836 deaths due to PC [3]. Increased public awareness and the ease of prostate-specific antigen (PSA) testing have led to PC being considered a public health priority in low-and middle-income settings [4]. In Latin America, the burden of PC follows the global trend [5], although with the existence of heterogeneity among the countries from this region [6].…”
Section: Introductionmentioning
confidence: 99%
“…During this same year, there were an estimated 1.41 million cases and 486,836 deaths due to PC [3]. Increased public awareness and the ease of prostate-specific antigen (PSA) testing have led to PC being considered a public health priority in low-and middle-income settings [4]. In Latin America, the burden of PC follows the global trend [5], although with the existence of heterogeneity among the countries from this region [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, official regulation on PCa-ED is ambitious and yet controversial. A recent insight of PCa-ED in Mexico was published by Lajous et al, and it's suggested that following the official normativity is challenging as Mexico probably lack the wanted infrastructure and resources to bear the extra burden of around 15 million men undergoing PCa-ED 18 . Following the authors' statements, we consider that outlining a PCa-ED national effort requires not only the PCP topics addressed here but also a collective endeavor along health institutions to provide a wider overview and determine the settings needed for this challenging situation.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo a Lajous et al, "la factibilidad de la evaluación del APE no está disponible de manera amplia en los países en vías de desarrollo o de ingresos medios como es México", (5) lo cual aumenta el problema de la detección oportuna.…”
Section: Discussionunclassified